Micellar Casein Production and Application in Dairy Protein Industry - Elena I. Melnikova; Ekaterina B. Stanislavskaya; Ekaterina V. Bogdanova; Ekaterina D. Shabalova (Техника и технология пищевых производств, 2022)
The modern food industry sees raw milk as a source of functional ingredients. Technologies of protein ingredients have a great scientific and practical importance because membrane fractionation methods preserve the native structure and properties of protein components. The resulting proteins have good fat profile, moisture retention, and emulsification characteristics, as well as perform some useful technological functions in food systems. They have no status of food additives and can be applied in various branches of food production. Unfortunately, the Russian food industry has no such technologies of its own. This article introduces some technological recommendations for the p roduction of domestic micellar casein concentrate. The research involved skim milk, commercial micellar casein concentrates from various manufacturers, curd samples with 9.0% of fat in dry matter, and Rossiysky cheese produced according to traditional formulation and technology. The experiment relied on standard research methods of physical and chemical analysis to establish the chemical composition of the samples, e.g., fractional composition of skim milk proteins, grain-size distribution, amino acid profile, etc. The study involved a comparative analysis of the chemical composition, as well as functional and technological properties of commercial micellar casein concentrates from various manufacturers. A set of experiments made it possible to define the thermal effect on raw material and to predict the prospects for usage of the new technology. Samples with a high ratio of casein:whey proteins and a moderately high heat treatment increased the curd and cheese yield by 10–12% in comparison with the traditional formulation. Samples with the maximal concentration of undenatured milk-serum protein nitrogen increased the yield of protein dairy products by 2–3% in comparison with other samples of micellar casein concentrates. The ratio of casein:whey proteins was 80:20 in skim milk obtained at PJSC Dairy “Voronezhsky”. The optimal pore diameter was ≥ 15 nm. As for the microbiological properties, QMA and OAMO was 6×104 CFU/dm3, and no pathogenic microorganisms were detected. Therefore, low-temperature pasteurization proved feasible at ≤ 76 ± 2°C and 10–15 s of hold time. The micellar casein concentrate added certain functional and technological properties to the finished product, depending on the specific application scope. The new technology will enable the domestic food industry to ov ercome the existing import dependence.